Necessities, environmental impact, and ecological sustainability of genetically modified (GM) crops - Kelvin Ngongolo; Gideon S. Mmbando (Discover Agriculture, 2025)
Abstract Addressing the global challenge of feeding a growing population amidst environmental degradation and climate instability necessitates innovative agricultural solutions. Genetically modified (GM) crops were developed to resist pests, diseases, and stresses, and to enhance nutrition. Indirectly, traits like Bacillus thuringiensis (Bt) pest resistance have reduced pesticide use, benefiting the environment. Nonetheless, persistent concerns revolve around their necessity, ecological footprint, and long-term viability. This study aims to explore the potential of GM crops in crop productivity chain, while scrutinizing issues like biodiversity loss and pesticide resistance. Employing a combination of literature review and empirical studies, our research informs decision-making and policy formulation. While GM crops offer transformative potential, they also raise significant ecological concerns. Achieving a balance between their advantages and environmental risks is imperative for ensuring sustainable agriculture and food security. Recommendations encompass further research on ecological sustainability, development of informed policy frameworks, and fostering collaboration among stakeholders.